PENGARUH ALGIFERT DAN CYCOCEL TERHADAP PERTUMBUHAN DAN PRODUKSI BAWANG PUTIH (Allium sativum L.) VARIETAS LUMBU PUTIH - , Sugiyanta; , Sudarsono; Siti Mufidah (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 1995)
This experiment was conducted to determine the effect of plant growth regulator (Cycocel) and algifert in growth and bulb production of garlic (Allium sativum L.) cv. 'Lumbu Putih'. The experiment was set up randomized complete block design. Treatments were consisted of combination of algifert and cycocel applications. Algifert treatments consisted of spraying 0 (A0), 2 (A1), 4 (A2), 6 (A3) and 8 (A4) ml/l algifert solution on to garlic plants, while cycocel treatments consisted of spraying 0 (C0), 500 (C1), 1000 (C2) and 1500 (C3) Cycocel solution. Algifert spraying was conducted at 3, 5, 7, 9, 11 week after planting, while cycocel was at 8 week and 10 week after palnting. Result of the experiments indicated algifert and cycocel treatments did not significantly affect growth and bulb yield of garlic. However, interaction affect of algifert and cycocel significantly reduced total number of cloves of each garlic bulb. Comparation mean analyzis showed A2C3 (algifert 4 ml/l with cycocel 1500 mg/l) treatment resulted in significantly lower total number of cloves of each garlic bulb than A2C0 or A2C1 (algifert 4 ml/l with or with out cycocel 500 mg/l) treatments, respectively. Treatment combination A2C3 significantly reduced the total number of cloves each bulb. However, the reduction of total number of cloes was not followed by increased in the size of the cloves. The result of the experiment also indicated the presence of positive correlation among parameters recorded. The total weight of harvested biomass were positively correlated with diameter of the bulb, number of clove, dry weight of the bulb, and dry matter contain of the bulb, respectively.